Steamboat Montana and the Opening of the West : History, Excavation, and Architecture - Corbin, Annalies (Book collections on Project MUSE., 2008)
The Montana was a shining example of modern design and technological sophistication when it made its maiden voyage in 1879. But only five years after it was launched, the Montana struck a railroad bridge and sank. The archaeological excavation of its wreckage offers a fascinating insight into Western expansion.